Correction: A Mixture of Delta-Rules Approximation to Bayesian Inference in Change-Point Problems. - Robert C Wilson; Matthew R Nassar; Gaia Tavoni; Joshua I Gold (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1003150.].